Are food taxes for healthy eating acceptable? A survey of public attitudes in the UK - Franco Sassi; Mario Martínez-Jiménez; Hannah Brinsden (BMJ Public Health, 2025)
Introduction Appropriately designed food taxes can improve diet quality and health. Fiscal levers are used in several countries to combat the rise in obesity and diet-related diseases. This study aims to investigate public attitudes, knowledge and policy preferences regarding food taxes for promoting healthy eating in the UK.Methods A survey was administered through YouGov Plc to a nationally representative sample of 2125 adults, gathering information on: acceptability and support for different types of food taxes, awareness and knowledge of existing taxes and preferences for the characteristics of possible new taxes.Results Overall, 48% of respondents support higher taxes on unhealthy foods, rising to 72% if taxes made healthy foods more affordable. Respondents with high socioeconomic status and those living in London showed the highest support. Respondents had limited awareness of existing food and beverage taxes and prioritised discretionary items such as cakes and crisps for possible increased taxation.Conclusions The survey shows a high level of support for taxing unhealthy foods, as well as concern for the affordability of healthy foods. A carefully designed holistic approach to food taxation can be part of a wider public health strategy and can be favourably met by the general population in the UK.